Building PRM in sub-Saharan Africa - Tannor, Abena Yeboaa; Nelson, Mary Elizabeth S.; Steere, Hannah K.; Quao, Benedict Okoe; Haig, Andrew J. (Frontiers in Rehabilitation Sciences, 2022)
It is estimated that about 50% of people in low- and middle- income countries who require rehabilitation do not get it. Multidisciplinary rehabilitation services led by Physical and Rehabilitation Medicine (PRM) physicians have been shown to improve functioning, independence, and the quality of life of persons with reduced functioning or disability. However, there is a dearth of PRM physicians in low to middle-income countries (LMICs), particularly in sub-Saharan Africa. One potential solution to this lack of specialists is the establishment of PRM training programs, which are currently lacking. The International Rehabilitation Forum developed and implemented a fellowship program to train physicians in rehabilitation medicine and has been successful in Ghana, Ethiopia, and Cameroon, all LMICs in sub-Saharan Africa. However, ongoing challenges include inadequate PRM trainers, availability of logistics and services for hands-on experience, and funding. The fellowship program has a promising future and an ultimate goal of having locally trained fellows leading the program and expanding it to other LMICs. There has however been no publication of the process followed to achieve this or of a similar process undertaken anywhere in Africa. The process followed in this publication highlights the journey from engaging stakeholders to the admission of new and current fellows in training.